Advancing methods for US transgender health research. Issue 2 (April 2016) - Reisner, Sari L.; Deutsch, Madeline B.; Bhasin, Shalender; Bockting, Walter; Brown, George R.; Feldman, Jamie; Garofalo, Rob; Kreukels, Baudewijntje; Radix, Asa; Safer, Joshua D.; Tangpricha, Vin; T'Sjoen, Guy; et al.
Abstract : Purpose of review: This article describes methodological challenges, gaps, and opportunities in US transgender health research. Recent findings: Lack of large prospective observational studies and intervention trials, limited data on risks and benefits of sex affirmation (e.g., hormones and surgical interventions), and inconsistent use of definitions across studies hinder evidence-based care for transgender people. Systematic high-quality observational and intervention-testing studies may be carried out using several approaches, including general population-based, health systems-based, clinic-based, venue-based, and hybrid designs. Each of these approaches has its strength and limitations; however, harmonization of research efforts is needed. Ongoing development of evidence-based clinical recommendations will benefit from a series of observational and intervention studies aimed at identification, recruitment, and follow-up of transgender people of different ages, from different racial, ethnic, and socioeconomic backgrounds and with diverse gender identities. Summary: Transgender health research faces challenges that include standardization of lexicon, agreed upon population definitions, study design, sampling, measurement, outcome ascertainment, and sample size. Application of existing and new methods is needed to fill existing gaps, increase the scientific rigor and reach of transgender health research, and inform evidence-based prevention and care for this underserved population.